Tetanus Toxoid Immunization Viewed From The Attitude And Family Support Of Pregnant Women At The Samkai Community Health Center - Indah Puspita Sari; Anggrawati Wulandari; Erma Retnaningtyas; Shanty Natalia (Journal of Health Science Community, 2024)
Tetanus infection is one of the causes of maternal and infant mortality. This study aims to determine Tetanus Toxoid Immunization in viewed from attitudes and family support of pregnant women at the Samkai Community Health Center. This study uses a research design Analytical Observational with approach cross sectional. With technique accidental sampling A sample of 57 respondents was obtained, the independent variable (attitude and family support) and the dependent variable (tetanus toxoid immunization) used a questionnaire. Statistical tests are used Chi-Square to find out the relationship between the two variables. The results of research from 57 respondents showed that mothers' attitudes regarding tetanus toxoid immunization were mostly negative, namely 37 respondents (64.9%), family support regarding tetanus toxoid immunization was mostly unsupportive, namely 32 respondents (56.1%), and most mothers did not receive complete tetanus toxoid immunization, namely 40 respondents (70.2%). Analysis using the Chi-Square statistical test showed that there was a relationship between tetanus toxoid immunization in terms of attitudes towards pregnant women with a p value = 0.001 < 0.05, and there was a relationship between tetanus toxoid immunization in terms of family support for pregnant women with a p value = 0.003 < 0.05. There is a need for health workers, especially midwives, to provide education about the importance of Tetanus Toxoid immunization and monitor the completeness of complete Tetanus Toxoid immunization, especially for pregnant women.